Ex Ante Impact Assessment of a Drought Tolerant Rice Variety in the Presence of Climate Change - Mottaleb KA; Rejesus RM; Mohanty S; Murty MVR; Li T; Valera GH; Gumma, Murali K. (2012)
Rice productivity and sustainability are continually threatened by abiotic stresses, particularly in the era of global climate change. In severe cases, 100% yield loss can be experienced due solely to abiotic stresses, such as drought. The situation may become worse due to climate change that may multiply the frequency and severity of such abiotic stresses. Hence, there is an urgent need to develop improved varieties that are more resilient to abiotic stresses. This study examines the net economic benefit and potential economic impacts of developing and disseminating a drought tolerant rice variety in South Asia. Drought is one of the most destructive abiotic stresses that not only causes major rice yield losses in South Asia, but also in other parts of Asia and Africa. Using the ORYZA2000 crop simulation model, we demonstrate that the new variety can provide yield gains in South Asia both when there is no change in the climate and also under the different climate scenarios projected by CGCM climate model. Moreover, our economic surplus analysis shows that the economic benefits from the successful development and dissemination of a drought tolerant variety more than outweigh the research investments needed to develop the variety. The partial equilibrium models we used also indicate that rice production is higher and rice prices are lower when a drought tolerant variety is adopted in South Asia (as compared to the case without this new variety). This in turn can lead to more sustainable rice production, improved food security, and better nutritional outcomes for the poor.